Yeast strains with technological and probiotic traits isolated from Mihalic cheese - Senses-Ergul, S. (2021)
The present work investigated the technological and probiotic characteristics of 20 yeast strains originating from Mihalic cheese. All isolates exhibited lipolytic activities. Proteolytic activity was detected only in the strains Geotrichum silvicola and Trichosporon asahii. While all isolates assimilated glucose, 85% and 40% of isolates also assimilated galactose and lactose, respectively. Furthermore, 55% and 25% of the strains were positive for glucose and galactose fermentation, respectively. Lactate assimilation was detected in 60% of the isolates. Most isolates were able to grow at 37°C and 4°C, while 40% were also able to grow at 45°C. All yeast strains could grow at pH 5.4 and 4.0, and 65% were also able to grow at a pH of 2.5. All isolates could grow at 5% and 10% sodium chloride and 11 of them grew at 15% salt concentration. Candida inconspicua and C. tropicalis were found to be the species that were most resistant to 0.3% (w/v) Ox-Bile. Eight isolates exhibited weak inhibitory effects on Staphylococcus aureus. Three strains belonging to C. famata var. famata, C. catenulata and G. silvicola weakly inhibited the growth of L. monocytogenes. Based on the desired technological characteristics, G. silvicola M15 and T. asahii M1 isolates showed potential as adjunct starters.